Perancangan dan Simulasi Power Supply Simetris pada Yenka - Husnul Ulfa; Zahra Dea Syafila; Tryadi Herlambang; Aliffa Nur Hasana; Nadhira Aliya Zahra (Jurnal Pendidikan Teknik Elektro, 2022)
This research was conducted to test the accuracy of the symmetric power supply circuit based on the data made in the table. Symmetrical power supply circuit is designed based on bipolar power supply, have wave power supply and full wave power supply. with the circuit test data made in the table. A power supply, also known as a dual output power supply, is a type of adapter in a circuit that produces two output voltages (output) in a balanced but opposite direction to ground (zero). when at the voltage level at the negative and positive terminals to ground (Reference) with a position of 180 ° inverse from each other. The power supply circuit can work from a symmetrical adapter circuit as a voltage reducer, to switch alternating or AC voltages so that they are reversed into direct or DC voltages. The current source of the power supply converts the alternating current from the AC power plant which is then converted into DC. In addition, the result of this output makes +Vcc and –Vcc. The power supply circuit plays an important role in electronic devices such as computers, phone chargers, and televisions. On a computer the power supply can be found on the cable that is connected to the supply. The power supply can also function to protect electronic components from damage that occurs due to electrical damage that occurs. Testing the accuracy of the symmetrical power supply circuit using the yenka simulator to support the research. This simulator has complete features that make it easier for researchers to assemble circuits. In the simulation of symmetrical power supply bipolar output, full wave power supply and have wave power supply.